(untitled) (Biological Sciences - PJSIR, 1996)
Studies were conducted on twenty five spring wheat varieties/lines in the greenhouse and the field, using completely randomized design and randomized complete block design, respectively. In the greenhouse soil water content and atmospheric relative humidity were controlled to achieve the following treatments:-1) unstressed, 2) root stress. 3) aerial stress and 4) root plus aerial stress. In the field experiment the crop was grown under naturally occurring stress (about 50 mm of rain in crop season). Data wererecorded on various seedling and mature plant traits to determine the extent of genetic variability among genotypes and interrelationships between the traits. The differ- ences among the varieties/lines were highly significant for all the traits. Almost all the values of genotypic correla- tions were greater than phenotypic ones. In the least and most stressed treatments survival rate, flag leaf area, number of stomata and leaf venation were positively and significantly correlated with grain yield. In the root stress treatment survival rate, root volume, root-shoot ratio, hygrophilic colloids, epidermal cell size and osmotic pressure were negatively but non-significantly correlated with grain yield. Maximum and significant genotypic correlation (0.79) was found between survival rate at root + aerial stress and number of stomata followed by 0.57 between root volume and hygrophilic colloids. Path coefficient analysis showed that leaf venation had the maximum (0.73) direct association with grain yield followed by survival rate at no water stress (0.42). Epidermal cell size had maximum indirect effect on grain yield through leaf venation.